Cinema hollywoodiano no século XXI: o ritmo em abordagem semiótica e os filmes mais vistos de 2001 a 2010 - Merenciano, Levi Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Both box office success and possible disaffection of canonical criticism, in fact, the Hollywoodian cinema is a theme not too attractive in Brazilian academic theses. In the surroundings of this relationship - sometimes contractual, sometimes controversy (since they involve different opinions amongst public, critics and art) - it is necessary to describe the semiotics strategies within the meaning processes inherent to the movies, in order to explain, by means semiotics visual processes theory, the organization of expression rhythms and content rhythms that contemporary Hollywood films are able to manifest. In explaining the organization of plane of content and plane of expression of the most viewed films on the first decade of this century it is possible to defend hypotheses on different types of film structure, as the incidence of paratactic and hypotactic rhythms (with predominantly syntagmatic or paradigmatic effects), which aspect can be continuous or discontinuous. These concepts have a starting point on the structuralism (Saussure, Roman Jakobson, Christian Metz) and an arrival point on discursive semiotics (Algirdas J. Greimas and Courtes Joseph), also on the plastic approach (Jean-Marie Floch ) and on the studies of rhythm (Louis Hébert). The corpus is organized from the most viewed films in the last decade, from 2001 to 2010 (according to Box Office Mojo website). A set of significant units (the relevant sequences) four most watched movies will be analized: James Cameron's Avatar (2009), Gore Verbinski's Pirates of the Caribbean (2006), Lee Unkrich's Toy Story 3 (2010) and Peter Jackson's Lord of the Rings (2003). In order to describe the processes of meaning in film language, semiotic principles will be established to help observe and analize the relevant structural and resemblances in the movies mentioned (when possible, comparing them to other visual and verbal visual objects), to indicate differences and ...

Tanto sucesso de bilheteria quanto possível desafeto da crítica canônica, de fato, o cinema hollywoodiano é um tema pouco presente em teses brasileiras. Nos entornos dessa relação, ora contratual, ora polêmica (entre público, crítica e arte), serão descritas as estratégias semióticas no âmbito dos processos de significação inerentes ao cinema, de maneira a explicar, a partir dos processos semióticos visuais, a organização dos ritmos de expressão e de conteúdo possíveis que os filmes de Hollywood contemporâneos são capazes de manifestar. Ao explicar a organização dos planos de conteúdo e de expressão dos filmes mais vistos na primeira década deste século, defendem-se hipóteses em torno dos diferentes tipos de estrutura fílmica, conforme a incidência de ritmos paratáticos e hipotáticos (com efeito predominantemente sintagmático ou paradigmático), de aspecto contínuo ou descontínuo. Essas noções terão como ponto de partida os conceitos estruturalistas (Saussure, Roman Jakobson, Christian Metz) e como ponto de chegada a semiótica discursiva (Algirdas J. Greimas e Joseph Courtés), a plástica (Jean-Marie Floch), e a do ritmo (Louis Hébert). O corpus é organizado a partir dos filmes mais vistos na última década, de 2001 a 2010 (segundo o site Box Office Mojo). Será examinado um conjunto de unidades significantes (as sequências relevantes) de quatro filmes mais vistos: Avatar (2009), de James Cameron, Piratas do Caribe - o baú da morte (2006), de Gore Verbinski, Toy story 3, de Lee Unkrich (2010), e O Senhor dos anéis - o retorno do rei, de Peter Jackson (2003). Tendo como meta a descrição dos processos de significação na linguagem cinematográfica, serão estabelecidos critérios semióticos que ajudem a observar as relações estruturais pertinentes nos filmes em questão (quando possível, comparando-os a outras semióticas visuais e verbovisuais), a fim de indicar diferenças e...
Keywords: Cinema; Semiotica; Ritmo; Rhythm; Los Angeles (Estados Unidos) Cinema